The prevalence of multiple sclerosis in Sicily. II: Agrigento city. Issue 2 (June 1981) - Dean, G; Savettieri, G; Giordano, D; Butera, C; Taibi, G; Morreale, S; Karhausen, L
Abstract : The prevalence of probable multiple sclerosis in Agrigento city on the south-west coast of Sicily is at least 2 per 100 000. This is likely to be a considerable underestimate of the true prevalence because the study presented particular difficulties in that the city is far from the neurological centres of Palermo. Catania, and Messina. There is no neurological department at either the general or the psychiatric hospital in Agrigento and there was a low awareness of the disease among the doctors in the city. Most of the patients were diagnosed in other centres. Agrigento is a good example of the difficulties of studying multiple sclerosis in a rural city which has no special interest in neurological problems and is far from a neurological centre. Studies in such centres must be pursued with great enthusiasm and over a long period of time, and all available sources of information in the city, medical and lay, and in other cities, must be utilised if a high proportion of the patients is to be found.